Analisis Sentimen Positif dan Negatif Pada Anteraja Selama Bulan Maret 2023 di Media Sosial Twitter - Aisyah Najla (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In running a company, there will definitely be positive and negative responses expressed by the public. Especially if the company often comes into contact with the community. One company that often comes into contact with the public is a company that operates in the field of goods delivery services. Of course, conditions that require goods delivery services to have direct contact with the public will result in a lot of news about goods delivery services. In order to analyze this news, researchers carried out media monitoring of one of the goods delivery service companies in Indonesia, namely, Anteraja. Media monitoring is a media management activity whose aim is to obtain information related to agencies or companies regarding public reactions to the messages conveyed. Monitoring is carried out by looking for news or information about company developments in the media. This activity was carried out to find out how much influence the news published has and the impact of the resulting news in the form of positive or negative sentiment expressed in the media. In this research, researchers carried out media monitoring of Anteraja using the Ripple10 tool with three steps, namely; (1) Inductive analysis to identify appropriate problems, (2) Data tracking and preparation, and (3) Sentiment analysis.